On the Lightweight Structural Design for Electric Road and Railway Vehicles using Fiber Reinforced Polymer Composites–A Review - Arifurrahman, Faizal; Budiman, Bentang; Aziz, Muhammad (Unijourn Publisher, 2018)
The main challenging issues of vehicles with electric propulsion are on the limited energy source due to relatively low battery capacity and low excitation of power traction. They can be tackled down by designing lightweight structures for frameworks and bodies of the vehicles. Composite materials which have a high strength to weight ratio are the best choice for designing and manufacturing the lightweight structures. A review of recent progress in utilization of the composite materials for electric vehicle structures is presented. It focuses on how the structures can support the electric vehicles to compete with internal combustion engine vehicles regarding their performance on the road. The utilization of composite material for structures of railway vehicles is also summarized. Furthermore, discussions are extended to the key technologies required for applying the composite materials in Indonesia such as composite–metal joint technology, fiber and matrix production technology, and numerical analysis competency for modeling the composite.